THE TREND OF CORROSIVE POISONINGS IN NORTH MACEDONIA – IS THERE A CHANGE IN THE PATTERN OF CORROSIVE POISONINGS? - Zanina Pereska; Niko Bekarovski; Lidija Petkovska; Natasha Simonovska; Aleksandra Babulovska; Kiril Naumoski; Kostadinoski, Kristin (My University, 2023)
Corrosive poisonings (CP) has remained highly presented in developing countries as opposite to the developed ones where they are declining. Objective was comparing the epidemiological characteristics of CP in the last two years to the predicted values (PV) calculated according previous 10 year-period trend analysis. There were 1668 acute CP from 2010 to 2021. CP decreased during the last 12 years period (y=-6.5+181.4, R2=0.56), increased by 1.5% during 2020 due to COVID-19 curfews, and decreased by 25.5% in 2021, compared to PV. Females increased during 2020 by 7.7% and then continued to decrease during 2021 by 27.5%, while males declined during 2020 and 2021 by 16.6% and 32.4% respectively, compared to PV, becoming almost equally represented in 2021. During 2020 and 2021 CP increased in adolescents (by 12.8% and 80.0%) and older than 75 years (by 2.5% and 6.2%), but not in adults who rose during 2020 by 3.7% and declined in 2021 by 17.9% compared to PV. The suicidal CP presented in proportion slightly rose (y=0.01x+0.56, R2= 0.07) during 12 years period, decreased in 2020 by 4.6% and increased by 9.9% in 2021 compared to PV. The CP declined during the last 12 years in North Macedonia with an increase in suicidal CP and more significant reduction in females compared to males. The age group patterns changed by increasing poisonings in adolescent and older the 75 years during the last two years, becoming target vulnerable groups that require increased medico-social attention.
Keywords: corrosive poisoning; trend; suicide